Penambahan tepung daun pegagan (Centella asiatika) terhadap performa produksi puyuh - Yuli Arif Tribudi; Arina Nurfianti (Faculty of Animal Science, Universitas Brawijaya, 2017)
The study of this research was to evaluate the effect of pegagan (Centellaasiatica) on quail production performance. The materials used in this studywere 200 quail phase layer Coturnix-coturnix japonica strain. The methodused was experimental design with completely randomized design (CRD) with 4treatments and 5 replications. The treatments in this study were the feedcontrol without the addition of pegagan meal (P0); 0.5% (P1); 1% (P2) and1.5% pegagan meal (P3). The variables observed were feed intake (g/bird /day);Hen Day Production (%); feed conversion and egg weight (g/bird/day). Theresults of this research showed that pegagan meal not effect significantly(P>0.01) on feed intake (g/bird/day), Hen day Production (%); feed conversionand egg wight (g/bird/day) in quail production performance.it can be concluedthat Feed intake, Hen day Production, feed conversion and egg wight was beston P3. 1,5% pegagan meal in the feed were advised